Job Allocation of Rajawali Mas Family Members Based on Miner’s Entrepreneurial Personalities and Myer-Briggs Type Indicator (MBTI) (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This research is conducted to allocate Rajawali Mas family members into a fit job position based on Miner’s Entrepreneurial Personalities and Myers-Briggs Type Indicator (MBTI). This research uses a quantitative descriptive research design. There are three participants chosen in this study, including the first generation of Rajawali Mas, the second generation of Rajawali Mas who join the business, and an expert in human resource management and family business. The questionnaire and interview are used to collect the data. The result of the study found that each family member who joined the Rajawali Mas business has different characteristics of entrepreneurship. Based on the Miner’s Test, Rajawali Mas family members possessed different types of entrepreneur route, such as the Personal Achiever, the Real Manager and the Expert Idea Generator, including a complex entrepreneur which is possessed by the CEO. Based on the MBTI, Rajawali Mas family member personality ranged to ISTJ, ESTJ, ESTP and ISFJ personality.